Impact of oocyte-secreted factors on its developmental competence in buffalo. Issue 3 (8th June 2017) - Gupta, Swati; Pandey, Sriti; Parmar, Mehtab S.; Somal, Anjali; Paul, Avishek; Panda, Bibhudatta S. K.; Bhat, Irfan A.; Baiju, Indu; Bharti, Mukesh K.; Saikumar, G.; Sarkar, Mihir; Chandra, Vikash; et al.
Summary: Oocyte-secreted factors (OSFs) play an important role in the acquisition of oocyte developmental competence through bidirectional cross-talk between oocyte and cumulus cells via gap junctions. Thus, the present study was designed to investigate the effect of two OSFs, growth differentiation factor 9 (GDF9) and bone morphogenetic protein 15 (BMP15), on the developmental competence of buffalo oocytes derived from two different follicle sizes. Cumulus–oocyte complexes (COCs) from large follicles (LF, >6 mm) or small follicles (SF, <6 mm) were collected and matured in vitro either in the presence of GDF9 or BMP15, or both, or with the denuded oocytes (DOs) as a source of native OSFs. Cleavage and blastocyst rates were significantly ( P < 0.05) higher in LF-derived than SF-derived oocytes. Cleavage and blastocyst rates were significantly higher ( P < 0.05) in the DOs and the combination groups compared with the control, GDF9 alone and BMP15 alone groups, both in LF-derived and SF-derived oocytes, although the cleavage and blastocyst rates did not differ significantly ( P > 0.05) between DOs and combination groups. Relative mRNA analysis revealed significantly higher ( P > 0.05) expression of the cumulus cell marker genes EGFR, HAS2, and CD44 in LF-derived than SF-derived oocyte; the expression of these markers was significantly higher ( P > 0.05) in DOs and combination groups, irrespective of the follicle size. These results suggested that LF-derived oocytes have a higher developmental competence than SF-derived oocytes and that supplementation of GDF9 and BMP15 modulates the developmental competence of buffalo oocytes by increasing the relative abundance of cumulus-enabling factors and thereby increasing cleavage and the quality of blastocyst production.